2020
DOI: 10.22219/jpbi.v6i2.12112
|View full text |Cite
|
Sign up to set email alerts
|

Implementing blended-problem based learning through Google classroom in biology learning

Abstract: Information technology is determinant factor in creating learning environment among the 21st Century generation. This qualitative descriptive research aimed to obtain theoretical views and empirical evidences of the blended-problem based learning (PBL) application. The data were collected through non-test technique through observation. The observations were made to analyze student activities in each step of the blended-PBL. In addition, the observations were also constructed to get a view of students' off-task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
3
0
2
Order By: Relevance
“…Salah satu LMS yang dikembangkan adalah google classroom. Google classroom menyediakan serangkaian fitur canggih yang menjadikannya alat yang ideal untuk berkomunikasi dengan siswa (Hikmawati & Suryaningsih, 2020). Gooogle classroom memberikan kebebasan kepada guru untuk berbagi materi dan memberikan tugas mandiri untuk siswa serta dapat membuka ruang diskusi untuk siswa secara daring (Asnawi, 2018).…”
Section: Pendahuluanunclassified
“…Salah satu LMS yang dikembangkan adalah google classroom. Google classroom menyediakan serangkaian fitur canggih yang menjadikannya alat yang ideal untuk berkomunikasi dengan siswa (Hikmawati & Suryaningsih, 2020). Gooogle classroom memberikan kebebasan kepada guru untuk berbagi materi dan memberikan tugas mandiri untuk siswa serta dapat membuka ruang diskusi untuk siswa secara daring (Asnawi, 2018).…”
Section: Pendahuluanunclassified
“…Hasil ini mendukung penelitian yang dilakukan oleh penelitian sebelumnya yang menyatakan bahwa model Problem Based Learning lebih efektif dalam pembelajaran tematik (Rilianti, 2019). Pembelajaran dengan model Problem Based Learning dapat menjadi pedoman dalam penerapan proses pembelajaran di sekolah khususnya di kelas III untuk meningkatkan hasil belajar siswa (Budi et al, 2020;Hikmawati & Suryaningsih, 2020). Implikasi dari penelitian ini menyajikan model Problem Based Learning yang dapat menjadi referensi bagi guru dalam memilih model pembelajaran yang dirasa belum sesuai dari model sebelumnya.…”
Section: Pembahasanunclassified
“…Relating to the effects of Task-based Learning on the students, several studies have been conducted indicated that the implementation of Task-based Learning in teaching English has positive effects on the students' communicative competence (Carolina & Campo, 2016;Kandari, 2020). On the other hand, related to the use of Google Classroom, studies by previous research showed that Google Classroom could assist the implementation of Problem-based Learning and students actively participated in the learning process (Hikmawati & Suryaningsih, 2020). A study by other previous study also revealed that the use of Google Classroom helped improve the average achievement of students and was capable of operating effectively and assisting the lecturers and students (Syakur, 2020).…”
Section: Introductionmentioning
confidence: 99%